Internalisasi Nilai Toleransi untuk Memperkuat Civic Disposition di Kelurahan Nyarumkop sebagai Kampung Moderasi Beragama - Jesika Nurula Ainur; Suharno; Bayu Putra Pamungkas (Lembaga Teewan Journal Solutions, 2026)
Tolerance is an important value in multicultural societies that plays a role in maintaining social harmony and strengthening civic character. The Nyarumkop sub-district, as a Religious Moderation Village, demonstrates the practice of tolerance that has been built into the social life of the community. This study aims to (1) describe the process of internalizing the value of tolerance in the community of Nyarumkop Village, (2) analyze the Religious Moderation Village as a manifestation of the practice of tolerance, and (3) explain the support of government policies and the role of religious leaders in maintaining the value of tolerance. This study uses a qualitative approach with a case study design through data collection techniques such as observation, interviews, and documentation. Data analysis was carried out through the stages of data collection, data reduction, data presentation, and conclusion drawing. The results show that (1) the internalization of tolerance values occurs through social habits such as mutual cooperation, interfaith dialogue, and participation in joint activities, (2) the Religious Moderation Village becomes a social space that strengthens harmonious interactions among residents, and (3) government policy support and the exemplary role of religious leaders play a role in maintaining and strengthening the practice of tolerance. This process contributes to the strengthening of civic disposition, which is reflected in social responsibility, active participation, and respect for diversity.